Lessons Learned: Transfer of the High‐Definition Circulating Tumor Cell Assay Platform to Development as a Commercialized Clinical Assay Platform. Issue 5 (22nd March 2017) - Kuhn, P; Keating, SM; Baxter, GT; Thomas, K; Kolatkar, A; Sigman, CC
Abstract : Planning and transfer of a new technology platform developed in an academic setting to a start‐up company for medical diagnostic product development may appear daunting and costly in terms of complexity, time, and resources. In this review we outline the key steps taken and lessons learned when a technology platform developed in an academic setting was transferred to a start‐up company for medical diagnostic product development in the interest of elucidating development toolkits for academic groups and small start‐up companies starting on the path to commercialization and regulatory approval.